Impact of pretreatment of the bulk starting material on the efficiency of liquid phase exfoliation of WS2 - Ott, Steffen; Lakmann, Melanie; Backes, Claudia (Nanomaterials, 2021)
Liquid phase exfoliation (LPE) is widely used to produce colloidal dispersions of nanomaterials, in particular two-dimensional nanosheets. The degree of exfoliation, i.e., the length to thickness aspect ratio was shown to be intrinsically limited by the ratio of in-plane to out-of-plane binding strength. In this work, we investigate whether simple pretreatment of the starting material can be used to change the in-plane to out-of-plane binding strength through mild intercalation to improve the sample quality in sonication-assisted LPE. Five different pretreatment conditions of WS2 were tested and the dispersions size-selected through centrifugation. From optical spectroscopy (extinction, Raman, photoluminescence), information on nanosheet dimension (average lateral size, layer number, monolayer size) and optical quality (relative photoluminescence quantum yield) was extracted. We find that the pretreatment has a minor impact on the length/thickness aspect ratio, but that photoluminescence quantum yield can be increased in particular using mild sonication conditions. We attribute this to the successful exfoliation of nanosheets with a lower degree of basal plane defectiveness. This work emphasizes the complexity of the exfoliation process and suggests that the role of defects has to be considered for a comprehensive picture.